2017
DOI: 10.2174/1872208311666170215151834
|View full text |Cite
|
Sign up to set email alerts
|

Patents on Endophytic Fungi

Abstract: In the last few years, research and inventions regarding the different aspects of endophytic fungi beneficial for host plant as well as for human beings have been carried out, which is supported by the increasing number of patents granted on endophytic fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Gokhale et al . () have enlisted several patents granted on different aspects of endophytic fungi. The commercial application of endophytic microbes for plant growth promotion and natural products is not as common as PGPR or mycorrhizae due to a range of scientific and technical challenges especially in formulations (Schönwandt et al .…”
Section: Resultsmentioning
confidence: 99%
“…Gokhale et al . () have enlisted several patents granted on different aspects of endophytic fungi. The commercial application of endophytic microbes for plant growth promotion and natural products is not as common as PGPR or mycorrhizae due to a range of scientific and technical challenges especially in formulations (Schönwandt et al .…”
Section: Resultsmentioning
confidence: 99%
“…Endophytic fungi have a higher potential to produce a wide variety of bioactive molecules that belong to various structural classes (such as alkaloids, peptides, steroids, terpenoids, phenols, quinones, and flavonoids). These chemical variety of fungi metabolites is associated with the inhibition of a wide variety of pathogenic microorganisms [ 7 - 9 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Endophyte research has stimulated the interest of the scientific community, as these microorganisms represent an important genetic source with the ability to produce metabolites with diverse biotechnological applications [ 7 - 9 ]. Several studies have shown that the colonization and distribution of the endophytic population in plant tissues are regulated by different properties such as environmental factors, microorganism-plant interactions and endophyte community interactions [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last 10 years it became apparent that endophytes are capable to produce the same bioactive secondary metabolites as their hosts and therefore there is a tremendous interest of the scientifi c community towards isolation, characterization and exploitation of endophytic fungi from medicinal plants as was judged by the amount of publications and number of patents (Gokhale et al, 2017). …”
Section: Discussionmentioning
confidence: 99%